Immigrant Legalization and the Redistribution of State Funds: Evidence from the 1986 IRCA - Navid Sabet; Christoph Winter (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the impact of immigrant legalization on fiscal transfers from state to local governments in the United States, exploiting variation in legal status from the 1986 Immigration Reform and Control Act (IRCA). State governments allocate more resources to IRCA counties, an allocation that is responsive to the electoral incentives of the governor. Importantly, the effect emerges prior to the enfranchisement of the IRCA migrants and we argue it is driven by the IRCA's capacity to politically empower already legal Hispanic migrants in mixed legal status communities. The IRCA increases turnout in large Hispanic communities as well as Hispanic political engagement, without triggering anti-migrant sentiment.
Keywords: J15; H72; P16; 330; distributive politics; state and local government; immigrant legalization